2015
DOI: 10.1002/ajpa.22724
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of neocortical ratios in stem primates

Abstract: Extant euprimates (=crown primates) have a characteristically expanded neocortical region of the brain relative to that of other mammals, but the timing of that expansion in their evolutionary history is poorly resolved. Examination of anatomical landmarks on fossil endocasts of Eocene euprimates suggests that significant neocortical expansion relative to contemporaneous mammals was already underway. Here, we provide quantitative estimates of neocorticalization in stem primates (plesiadapiforms) relevant to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 43 publications
7
39
0
Order By: Relevance
“…() suggested that the neocortical surface area increased through time in rodents as has been shown for primates (Long et al. ), but this increase was less intense in rodents and started later. In the context of this paper, it is of interest to compare the data from the sciurid C. wilsoni with data from primates that are roughly contemporaneous: Oligocene anthropoids.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…() suggested that the neocortical surface area increased through time in rodents as has been shown for primates (Long et al. ), but this increase was less intense in rodents and started later. In the context of this paper, it is of interest to compare the data from the sciurid C. wilsoni with data from primates that are roughly contemporaneous: Oligocene anthropoids.…”
Section: Discussionmentioning
confidence: 82%
“…Nevertheless, data on neocortical surface area in primates have been published, and a trend in neocortical surface area increase has been demonstrated for this group (Long et al. ). For rodents, a similar trend can be inferred based on the results of this and previous studies (Bertrand et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations